2021
DOI: 10.1016/j.fochx.2021.100139
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention with a tea from hawthorn (Crataegus oxyacantha) leaves and flowers attenuates colitis in rats by reducing inflammation and oxidative stress

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The cell lysate was diluted twice with PBS and then stored at 4 °C. Based on previous reports ( Nascimento et al., 2021 ), CAT activity and MDA levels were evaluated. All of the tests were carried out according to the manufacturer's standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…The cell lysate was diluted twice with PBS and then stored at 4 °C. Based on previous reports ( Nascimento et al., 2021 ), CAT activity and MDA levels were evaluated. All of the tests were carried out according to the manufacturer's standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…The total saponins content of PNL and FPNL were assayed by the vanillin and glacial acetic acid method ( 19 ). 1.5 mg ginsenoside Re standard was weighed and added to a 6 ml methanol solution to dissolve entirely.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, it could also significantly lower plasma levels of TNF‐α and monocyte chemoattractant protein 1 (MCP‐1) and downregulate the hepatic expression of MCP‐1 and IL‐1β in type 2 diabetes (T2D) rats (He et al., 2021). Moreover, the hawthorn pulp could reduce plasma myeloperoxidase, C‐reactive protein, and alkaline phosphatase (ALP) levels, suggesting its potential to block or regulate intestinal inflammation in a castor oil–induced rat model (Nascimento et al., 2021; Sammari et al., 2021). In addition, a series of animal experiments have demonstrated that hawthorn pulp can alleviate chronic diseases associated with inflammation, such as osteoarthritis, ulcerative colitis, atherosclerosis (AS), chronic heart failure, hepatic fibrosis, and obesity, but the specific mechanism of action has not yet been completely revealed (Alsharif et al., 2022; Cheng et al., 2020; Hamza et al., 2020; He et al., 2021; Nguyen et al., 2021).…”
Section: Bioactivities Based On In Vitro and In Vivo Studiesmentioning
confidence: 99%